2010
DOI: 10.1002/app.30171
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of mica‐filled PBT/ABAS composites

Abstract: Tensile properties and Izod impact strength of mica-filled composites of poly(butylene terephthlate) (PBT)/polyacrylonitrile-butyl acrylate-styrene (ABAS) were studied at mica concentration range 0 to 0.14 volume fraction, (U f ). Tensile properties such as tensile modulus, strength, and breaking strain were normalized by dividing the data with the crystallinity (%) of the major component PBT in the composites and the matrix blends. The normalized relative tensile properties were compared with simple models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…With untreated clay [ 50 ] and graphene [ 39 ] in amorphous PET, the impact resistance decreased well below that of the unfilled plastic with an increase of filler loading. A similar trend is seen with mica in polyphenylene oxide [ 47 ], mica in PBT [ 55 ], and talc in PP [ 56 ], and in a conductive plastic of acrylonitrile-butadiene-styrene (ABS) filled with 1–5 vol.% of chopped steel fibres [ 7 ].…”
Section: Resultssupporting
confidence: 60%
“…With untreated clay [ 50 ] and graphene [ 39 ] in amorphous PET, the impact resistance decreased well below that of the unfilled plastic with an increase of filler loading. A similar trend is seen with mica in polyphenylene oxide [ 47 ], mica in PBT [ 55 ], and talc in PP [ 56 ], and in a conductive plastic of acrylonitrile-butadiene-styrene (ABS) filled with 1–5 vol.% of chopped steel fibres [ 7 ].…”
Section: Resultssupporting
confidence: 60%
“…Some works reported that the presence of mica platelets restricts the mobility or deformability of PVC molecules and consequently leads to an increase of elastic modulus 28–30. According to Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Although the addition of llers can improve the ame retardancy of the composites, it probably also greatly deteriorate the mechanical properties of the materials due to the promoted cracks spread in polymer matrix induced by llers. 36,37 It has been conrmed that the microlayer coextrusion technology can greatly alleviate the negative effect of the deteriorate in the mechanical properties of the composites due to the addition of the ller. 38,39 Therefore, in this work, tensile tests are performed to investigate the inuence of EG ller orientation and dispersion on the tensile strength and elongation at break of TPU composites.…”
Section: Mechanical Propertiesmentioning
confidence: 99%